Los Angeles and the Automobile : The Making of the Modern City - Bottles, Scott L. (Book collections on Project MUSE., 1987)
More comprehensive than any other book on this topic, Los Angeles and the Automobile places the evolution of Los Angeles within the context of American political and urban history.